Seed priming with ascorbic acid enhances salt tolerance in micro-tom tomato plants by modifying the antioxidant defense system components - Alves, Rita de C. [UNESP]; Rossatto, Davi R. [UNESP]; da Silva, Jeferson dos S. [UNESP]; Checchio, Mirela V. [UNESP]; de Oliveira, Kevein R. [UNESP]; Oliveira, Francisco de A.; de Queiroz, Samira F. [UNESP]; da Cruz, Mara C.P. [UNESP]; Gratão, Priscila L. [UNESP] (Elsevier, 2021)
Although ascorbic acid (AsA) has been known to improve plant defense system components against salt stressful-conditions, little is known about physiological and biochemical responses of AsA-mediated alleviation of salt stress in tomatoes. The main objective of this work was, therefore, to explore the role of ascorbic acid application via seed priming on antioxidant defense responses and growth and fruit yield regulation in tomato Micro-Tom under salt stress. The experiment was carried out using a 2 × 2 factorial completely randomized design with four replicates. In this way, seed priming with AsA (0 and 100 mM AsA) was used in Micro-Tom seeds to improve the tolerance of subsequent salt-stress exposure (0 and 100 mM NaCl). The AsA priming effect was assessed on subsequent exposure to salt stress conditions with a physiological and biochemical approaches, involving antioxidant responses. Overall results indicated that AsA plays a role in alleviating the negative effects of salt stress by increasing water potential and water use efficiency, reducing Na+ content, lipid peroxidation and H2O2 content, and increasing total pigments content, superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), peroxidase (POX), glutathione peroxidase (GPX) and glutathione reductase (GR) activities and GSH content, leading to better plant growth and higher yields. Thus, our results indicated that priming with AsA is an efficient management technique that can be used to alleviate the deleterious effects of salt stress and enhance the salt tolerance of Micro-Tom plants by modulation of antioxidant mechanisms.
Keywords: Antioxidant defense; Oxidative stress; Plant growth; Salt tolerance